Live-action role-playing and the affordances of social media - Bjärstorp, Sara; Ragnerstam, Petra (Culture Unbound, 2023)
Live-action role-playing (larp) is characterized by participants’ physical and mental immersion in a storyworld, played out in a specific location during a fixed period of time. Most of the immersion is realized during the live event itself, where a collective story is acted out in physical space in real time. However, contemporary larping also usually entails significant interaction and communication between players, and between players and organisers, before and after the event itself, through digital media. In this article, we explore the social media afterlife of one of the most significant Nordic larp events in recent years, Fortune and Felicity (2017). Using an affordance framework, we discuss what happens to the “liveness” of the larp when it is extended into social media. Through the affordances of persistence, visibility, editability and associability, we analyse material from the Facebook group connected to Fortune and Felicity, used by players and organisers to prepare for the larp and, afterwards, to continue the gameplay and to de-brief. In social media, the continuum of time and space, which is characteristic of the larp event itself, is changed into asynchronous and physically separate player action. Thus, the affordances of social media, we argue, enable player interaction and collaborative storytelling in ways that change the narrative, interactive and immersive dynamics of the larp.